Efforts to Improve Children's Fine Motor Skills through Sewing Activities at Raudhatul Athfal 'Aisyiyah Gontor - Sari, Heni Puspita; Sa'diah, Kalimatu (MANDAILING GLOBAL EDUKASIA, 2025)
Children, especially early childhood, are the most optimal period for development. For children, motor development greatly influences other aspects of development. Therefore, researchers took steps to improve children's fine motor skills through sewing activities. The purpose of this improvement is to improve children's fine motor skills through sewing activities in group B at RA 'Aisyiyah Gontor Mlarak Ponorogo in the 2022/2023 academic year. This research was conducted at Raudhatul Athfal 'Aisyiyah Gontor in the 2022/2023 academic year with 20 students. The implementation of this research used 2 cycles. Each cycle 5 RPPH (5 meetings). In cycle II, the aspects assessed experienced an increase. Through sewing activities, the results obtained increased in children's sewing abilities, namely in cycle I, children who had one star were 20%, children who had two stars 65%, children who had three stars 15%, children who had four stars 0%. In cycle II, children who have one star are 0%, children who have two stars are 15%, children who have three stars are 70%, children who have four stars are 15%. Thus, this research experienced an increase in cycle II.